2011 23rd Euromicro Conference on Real-Time Systems 2011
DOI: 10.1109/ecrts.2011.20
|View full text |Cite
|
Sign up to set email alerts
|

Is Semi-Partitioned Scheduling Practical?

Abstract: Semi-partitioned schedulers are-in theory-a particularly promising category of multiprocessor real-time scheduling algorithms. Unfortunately, issues pertaining to their implementation have not been investigated in detail, so their practical viability remains unclear. In this paper, the practical merit of three EDF-based semi-partitioned algorithms is assessed via an experimental comparison based on real-time schedulability under consideration of real, measured overheads. The presented results indicate that sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…With big overhead values, generally the platforms become more unschedulable under MRPS. This is an important factor which makes the MRPS algorithm suitable for multiprocessor platforms with tasks having small working set size (WSS) [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With big overhead values, generally the platforms become more unschedulable under MRPS. This is an important factor which makes the MRPS algorithm suitable for multiprocessor platforms with tasks having small working set size (WSS) [3].…”
Section: Discussionmentioning
confidence: 99%
“…Once the job executes its critical section at destination processor, it will migrate back to its dedicated processor (source processor). As a result of migrations, the subtasks will incur overhead mainly due to cache-related migration delay [3]. This overhead is caused due to additional cache misses that a job incurs when resuming execution after a migration.…”
Section: Migration-based Synchronization Protocolmentioning
confidence: 99%
“…Following these observations, recent research has emerged and new scheduling algorithms appeared which aim to reduce the overheads by bounding the amount of preemptions (Bastoni et al, 2011;Nelissen et al, 2012). Also, a few studies have shown that avoiding co-scheduling tasks that heavily use a shared cache can reduce the overall execution time (Fedorova et al, 2006;Anderson et al, 2006).…”
Section: Motivationmentioning
confidence: 99%
“…In that case, there is a single queue of ready tasks and a single scheduler for all the processors. Finally, as a compromise that aims to alleviate limitations of partitioned (limited achievable processor utilization) and global (non-negligible overheads) algorithms, hybrid policies such as semi-partitioned and clustered scheduling have been proposed more recently (Bastoni et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Despite it being a complete workload, it does not provide any data analysis. Bastoni et al (2011) studied semi-partitioned schedulers in depth, evaluating the scheduling overhead, the cache-induced delays and other metrics with LITMUS RT (Calandrino et al 2006). While both rt-muse and (Bastoni et al 2011) use traces of events to analyze the behavior of schedulers, LITMUS RT aims at simplifying the implementation of complex scheduling policies, while rt-muse aims at closing the gap between theory and implementation by exposing the real-time characteristics of already implemented schedulers.…”
Section: Related Workmentioning
confidence: 99%